Answer

Verified

437.4k+ views

**Hint:**Here, we will take that \[h = {\csc ^{ - 1}}\left( {\dfrac{1}{{2{x^2} - 1}}} \right)\] and \[g = \sqrt {1 - {x^2}} \]. Then we will use that when \[h\] is differentiated with respect to \[g\], we have to calculate the value of \[\dfrac{{dh}}{{dg}}\]. After differentiating \[h\] with respect to \[x\] and \[g\] with respect to \[x\], we will divide them to find the required value.

**Complete step-by-step answer:**Let us assume that \[h = {\csc ^{ - 1}}\left( {\dfrac{1}{{2{x^2} - 1}}} \right)\] and \[g = \sqrt {1 - {x^2}} \].

We know that when \[h\] is differentiated with respect to \[g\], we have to calculate the value of \[\dfrac{{dh}}{{dg}}\].

Differentiating the equation \[h\] with respect to \[x\], we get

\[ \Rightarrow \dfrac{{dh}}{{dx}} = \dfrac{d}{{dx}}\left( {{{\csc }^{ - 1}}\left( {\dfrac{1}{{2{x^2} - 1}}} \right)} \right)\]

Using the property, \[{\csc ^{ - 1}}x = {\sin ^{ - 1}}\left( {\dfrac{1}{x}} \right)\] in the above equation, we get

\[

\Rightarrow \dfrac{{dh}}{{dx}} = \dfrac{d}{x}\left( {{{\sin }^{ - 1}}\left( {2{x^2} - 1} \right)} \right) \\

\Rightarrow \dfrac{{dh}}{{dx}} = \dfrac{d}{x}\left( {\dfrac{\pi }{2} - {{\cos }^{ - 1}}\left( {2{x^2} - 1} \right)} \right) \\

\Rightarrow \dfrac{{dh}}{{dx}} = \dfrac{d}{x}\left\{

\dfrac{\pi }{2} - 2{\cos ^{ - 1}}x{\text{ , if 0 < x < 1}} \\

\Rightarrow - \dfrac{{3\pi }}{2} + 2{\cos ^{ - 1}}x{\text{ , if - 1 < x < 0}} \\

\right. \\

\Rightarrow \dfrac{{dh}}{{dx}} = \left\{

\dfrac{d}{{dx}}\left( {\dfrac{\pi }{2} - 2{{\cos }^{ - 1}}x} \right){\text{ , if 0 < x < 1}} \\

\dfrac{d}{{dx}}\left( { - \dfrac{{3\pi }}{2} + 2{{\cos }^{ - 1}}x} \right){\text{ , if - 1 < x < 0}} \\

\right. \\

\]

Using the value, \[\dfrac{d}{{dx}}{\cos ^{ - 1}}x = \dfrac{1}{{\sqrt {1 - {x^2}} }}\] in the above equation, we get

\[ \Rightarrow \dfrac{{dh}}{{dx}} = \left\{

\dfrac{2}{{\sqrt {1 - {x^2}} }}{\text{ , if 0 < x < 1}} \\

\dfrac{{ - 2}}{{\sqrt {1 - {x^2}} }}{\text{ , if - 1 < x < 0}} \\

\right.{\text{ ......eq.(1)}}\]

Differentiating the equation \[g\] with respect to \[x\], we get

\[ \Rightarrow \dfrac{{dg}}{{dx}} = \dfrac{d}{{dx}}\left( {\sqrt {1 - {x^2}} } \right)\]

Using the property, \[\dfrac{d}{{dx}}{x^n} = n{x^{n - 1}}\] in the above equation, we get

\[ \Rightarrow \dfrac{{dg}}{{dx}} = \dfrac{{ - x}}{{\sqrt {1 - {x^2}} }}{\text{ ......eq.(2)}}\]

Dividing the equation (1) by equation (2), we get

\[

\Rightarrow \dfrac{{dh}}{{dg}} = \left\{

\dfrac{2}{{\sqrt {1 - {x^2}} }} \times \dfrac{{\sqrt {1 - {x^2}} }}{{ - x}}{\text{ , if 0 < x < 1}} \\

\dfrac{{ - 2}}{{\sqrt {1 - {x^2}} }} \times \dfrac{{\sqrt {1 - {x^2}} }}{{ - x}}{\text{ , if - 1 < x < 0}} \\

\right. \\

\Rightarrow \dfrac{{dh}}{{dg}} = \left\{

\dfrac{2}{{ - x}}{\text{ , if 0 < x < 1}} \\

\dfrac{{ - 2}}{{ - x}}{\text{ , if - 1 < x < 0}} \\

\right. \\

\Rightarrow \dfrac{{dh}}{{dg}} = \left\{

- \dfrac{2}{x}{\text{ , if 0 < x < 1}} \\

\dfrac{2}{x}{\text{ , if - 1 < x < 0}} \\

\right. \\

\]

Since we know that \[0 < \dfrac{1}{2} < 1\], so it lies on the upper parts of the above equation.

Taking \[x = \dfrac{1}{2}\] in the above equation, we get

\[

\Rightarrow {\left. {\dfrac{{dh}}{{dg}}} \right|_{x = \dfrac{1}{2}}} = - \dfrac{2}{{\dfrac{1}{2}}} \\

\Rightarrow {\left. {\dfrac{{dh}}{{dg}}} \right|_{x = \dfrac{1}{2}}} = - 4 \\

\]

**Note:**You should be familiar with the basic properties of differentiation and trigonometric functions, like \[{\csc ^{ - 1}}x = {\sin ^{ - 1}}\left( {\dfrac{1}{x}} \right)\] and \[\dfrac{d}{{dx}}{\csc ^{ - 1}}x = \dfrac{1}{{\sqrt {1 - {x^2}} }}\]. Students get confused to find the derivative and end up computing with respect to \[x\], which is wrong. A function can only be differentiated with respect to another function if and only if both the functions are dependent on the same variable. The key point is to use the differentiation properly to find the final answer.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Mark and label the given geoinformation on the outline class 11 social science CBSE

When people say No pun intended what does that mea class 8 english CBSE

Name the states which share their boundary with Indias class 9 social science CBSE

Give an account of the Northern Plains of India class 9 social science CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Trending doubts

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Which are the Top 10 Largest Countries of the World?

Difference Between Plant Cell and Animal Cell

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

How do you graph the function fx 4x class 9 maths CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Change the following sentences into negative and interrogative class 10 english CBSE